The use of warehouse automation technology for scalable and low-cost direct air capture - McQueen, Noah; Drennan, David (Frontiers in Climate, 2024)
Direct Air Capture (DAC) offers a promising pathway for combating climate change by removing carbon dioxide (CO2) directly from the atmosphere. Here, we discuss Heirloom's approach to DAC, which uses naturally occurring minerals, namely, calcium carbonate (CaCO3), in a cyclic process that leverages warehouse automation systems previously developed for large warehouses. The integration of DAC with warehouse automation systems unlocks a degree of manufacturability, scalability, operational efficiency, and financial viability. For successful scaling, DAC technologies and project developers must think through key scalability constraints, including modularity, constructability, supply chains, and leveraging existing infrastructure.